rHARM: accretion and ejection in resistive GR-MHD - Qian, Qian; Fendt, Christian (The astrophysical journal, 2017)
Turbulent magnetic diffusivity plays an important role for accretion disks and the launching of disk winds. We have implemented magnetic diffusivity and respective resistivity in the general relativistic MHD code HARM. This paper describes the theoretical background of our implementation, its numerical realization, our numerical tests, and preliminary applications. The test simulations of the new code rHARM are compared to an analytic solution of the diffusion equation and a classical shock tube problem. We have further investigated the evolution of the magnetorotational instability (MRI) in tori around black holes (BHs) for a range of magnetic diffusivities. We find an indication for a critical magnetic diffusivity (for our setup) beyond which no MRI develops in the linear regime and for which accretion of torus material to the BH is delayed. Preliminary simulations of magnetically diffusive thin accretion disks around Schwarzschild BHs that are threaded by a large-scale poloidal magnetic field show the launching of disk winds with mass fluxes of about 50% of the accretion rate. The disk magnetic diffusivity allows for efficient disk accretion that replenishes the mass reservoir of the inner disk area and thus allows for long-term simulations of wind launching for more than 5000 time units.
Published 2016 December 28
Gesehen am 22.01.2019